The Promise and Challenges of Intensive Longitudinal Designs for Imbalance Models of Adolescent Substance Use - Lydon-Staley, David M.; Bassett, Danielle S. (Frontiers in Psychology, 2018)
Imbalance models of adolescent brain development attribute the increasing engagement in substance use during adolescence to within-person changes in the functional balance between the neural systems underlying socio-emotional, incentive processing, and cognitive control. However, the experimental designs and analytic techniques used to date do not lend themselves to explicit tests of how within-person change and within-person variability in socio-emotional processing and cognitive control place individual adolescents at risk for substance use. For a more complete articulation and a more stringent test of these models, we highlight the promise and challenges of using intensive longitudinal designs and analysis techniques that encompass many (often greater than 10) within-person measurement occasions, thereby allowing an examination of within-person change and within-person variability. Use of intensive longitudinal designs will lend researchers the tools required to make within-person inferences in individual adolescents that will ultimately align imbalance models of adolescent substance use with the methodological frameworks used to test them.